Respon Empat Varietas Bayam terhadap Azotobacter dan Rhizobium - Rennanti Lunnadiyah Aprilia; Khanifatun Mu’minah (Journal of Horticulture Production Technology, 2026)
Excessive dependence on inorganic fertilizers in spinach cultivation may reduce soil quality; therefore, more environmentally friendly fertilization alternatives, such as biofertilizers, are needed. However, information on the effectiveness of Azotobacter and Rhizobium across different spinach varieties remains limited. This study aimed to evaluate the effects of biofertilizer type and variety on the growth and biomass of spinach. The experiment was conducted from February to July 2025 using a 2 × 4 factorial randomized complete block design with three replications. The first factor was biofertilizer type, consisting of Azotobacter (H1) and Rhizobium (H2), while the second factor was spinach variety, namely green spinach (V1), uproot spinach (V2), red spinach (V3), and batik spinach (V4). Observed variables included leaf number, plant height, leaf area, root length, plant fresh weight, root fresh weight, plant dry weight, and root dry weight. Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test at the 5% level. Variety had a highly significant effect on almost all parameters, except root length. The interaction between biofertilizer and variety had a highly significant effect on leaf number, plant height, leaf area, plant dry weight, and root dry weight, and a significant effect on plant fresh weight and root fresh weight. The best shoot performance was obtained from H1V1, with 14.44 leaves, plant height of 26.94 cm, leaf area of 637.22 cm², and plant dry weight of 1.66 g, whereas the highest root fresh weight was recorded in H2V3 at 5.09 g.